Evaluation of marginal and internal adaptations of posterior all-ceramic crowns fabricated with chair-side CAD/CAM system: an in vitro study - Merve Bankoğlu Güngör; Aylin Doğan; Bilge Turhan Bal; Seçil Karakoca Nemli (Gazi University, 2018)
Objective: Advances in chair-side Computer-Aided Design / Computer-Aided Manufacturing (CAD/CAM) technology and materials science currently enable the fabrication of highly esthetic restorations for the anterior and posterior teeth. However, there is a lack of evidence regarding the marginal and internal adaptations of new CAD/CAM materials. The objective of this study was to evaluate the marginal and internal adaptations of posterior all-ceramic restorations fabricated from contemporary restorative materials with chair-side CAD/CAM system. Materials and Method: An artificial mandibular left first molar tooth was prepared according to standard tooth preparation procedures, and standard models of the prepared teeth were obtained. All-ceramic restorations (n=10) were fabricated from seven different CAD/CAM blocks (IPS e.max CAD, Lava Ultimate, Incoris TZI, Incoris ZI, Vita Suprinity, Vita Enamic, and GC Cerasmart). The marginal and internal adaptations were measured with silicone replicas, which were sectioned with a thin lancet. The discrepancy between the die and the inner surface of the restoration was examined at 50× magnification by using a light microscope with digital camera. Four reference points were examined at each buccal-lingual section and eight reference points were examined at each mesial-distal section. The results were evaluated by two-way analysis of variance (ANOVA) followed by Tukey HSD test (α=0.05). Results: The values obtained from marginal-internal areas were generally greater than those in the marginal areas. Significant differences were found between the materials. The statistical analysis revealed that there was an interaction between the material type and the location of the reference points (p<0.05); the lowest values were observed in axial areas, and the highest values were observed in occlusal areas. Conclusion: All materials showed low marginal and internal discrepancies which were considered clinically acceptable.